Inulin supplementation in feed as a prebiotic for red tilapia Oreochromis sp. - Agustina Agustina; Adi Susanto (Jurnal Akuakultur Indonesia)
The objective of this study was to assess the impact of inulin as a prebiotic in feed on red tilapia (Oreochromis sp.) growth performance, hematological parameters, feed utilization, digestive enzyme activity, and the quantity of lactic acid bacteria in the intestine. This study has a fully randomized design with four treatments and three replications, namely inulin at doses of 0, 1, 2, and 4 g/kg feed. One-way ANOVA was used to assess data on growth performance, feed utilization, survival rate, digestive enzyme activity, and the amount of lactic acid bacteria, while the hematological parameters were analyzed descriptively. Red tilapia fry weighing an average of 5.27 ± 0.45 g was raised for 30 days in plastic container containing 40 L of water at a density of 15 fish per container (375 fish/m3). Fish were fed three times a day at satiation. Red tilapia-fed diet supplemented with 4 g/kg inulin of feed had higher body weight increase, protein efficiency ratio, digestive enzyme activity, and amount of lactic acid bacteria while food conversion ratio was lower compared to other treatments (p<0.05). Meanwhile, the specific growth rate and survival rate were not different from the control group. Hematological parameters were within the normal range for all treatments. Thus, the supplementation of inulin in feed of 4 g/kg has the potential as a prebiotic for red tilapia.